GRICE’S MAXIMS IN HUMOUR: THE CASE OF “HOME WITH KIDS” - Zhao Xue; Kuang Ching Hei (University of Kuningan, 2017)
Sitcoms provide entertainment, one of which is through humour. Using Grice’s (1975) non-observance of Cooperative Principles – flouting, violating, infringing, opting out, and suspending as framework for analysis, this study aims to investigate whether the non-observance of Grice’s (1975) maxims can contribute to the humorous effects seen in the Chinese sitcom “Home with Kids (Season 4)”. Specifically, this study aims to detect which of the maxims play an important role in creating humour. Data were compiled from 96 episodes of the show. A comparison of the non-observance was made before findings were qualitatively presented. The findings revealed that flouting and violating were used most frequently to create humour. The outcome of this study will have beneficial effects for L2 learners of Mandarin by enabling them to comprehend Chinese humour. The implications derived from this study suggest that humour may be created differently due to cultural differences. Keywords: Chinese sitcoms, humour, flouting, violation, non-observance, maxims